Processing of Sr2+ Containing Poly L-Lactic Acid-Based Hybrid Composites for Additive Manufacturing of Bone Scaffolds - Melo, Priscila; Naseem, Raasti; Corvaglia, Ilaria; Montalbano, Giorgia; Pontremoli, Carlotta; Azevedo, António; Quadros, Paulo; Gentile, Piergiorgio; Ferreira, Ana Marina; Dalgarno, Kenneth; Vitale-Brovarone, Chiara; Fiorilli, Sonia (Frontiers in Materials, 2020)
Composite materials represent one of the major areas of investigation for bone tissue engineering due to their tuneable compositional and mechanical properties, which can potentially mimic those of bone. Alongside this, the use of biodegradable materials has reduced the need for surgery to remove implants, mitigating the risks for the patient and reducing the overall clinical costs. In addition, the introduction of additive manufacturing technologies (AM) in the field of bone tissue engineering enables a strict control over the final morphological features of the scaffolds. In this scenario, the optimisation of 3D printable resorbable composites, made of biocompatible polymers and osteoinductive inorganic phases, offers the potential to produce a chemically and structurally biomimetic implant, which will resorb over time. The present work focuses on the development and process optimisation of two hybrid composite filaments to be used as feedstock for the fused filament fabrication (FFF) AM process. A Poly L-lactic acid (PLLA) matrix was blended with either nanohydroxyapatite (nano-HA) or mesoporous bioactive glasses (MBGs), both partially substituted with strontium (Sr2+), due to the well-known pro-osteogenic effect of this ion. Nano-HA with a 50% mol. of Sr2+ substitution showed a rod-like morphology, and a (Ca+Sr)/P ratio similar to the stoichiometric HA. Sol-gel produced MBGs displayed a spherical morphology, regular mesoporous structure and successful Sr2+ substitution (10% molar) into the framework. Both inorganic phases were incorporated into PLLA using a combination of manual blending and twin-screw extrusion processes. Both inorganic phases were homogeneously distributed throughout the polymer and preserved the ability to release Sr2+, essential to promote the required pro-osteogenic effect. The filament mechanical properties were not hindered after the incorporation of the inorganic phases, resulting in tensile strengths and moduli within the range of cancellous bone, 50 ± 10 MPa and 3 ± 1 GPa. Finally, the rheological characterization of the hybrid composites indicated a shear thinning behaviour, ideal for the processing with FFF, proving the potential of these materials to be processed into 3D structures aiming bone regeneration.